Outcomes and Health Care Utilization After Early Hospital Dismissal in Kidney Transplantation: An Analysis of 1001 Consecutive Cases. Issue 2 (8th June 2020) - Calderon, Esteban; Chang, Yu-Hui; Chang, James M.; Velazco, Cristine S.; Giorgakis, Emmanouil; Srinivasan, Ananth; Moss, Adyr A.; Khamash, Hasan; Heilman, Raymond; Reddy, Kunam S.; Mathur, Amit K.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To understand whether reduced lengths of stay after kidney transplantation were associated with excess health care utilization in the first 90 days or long-term graft and patient survival outcomes. Background: Reducing length of stay after kidney transplant has an unknown effect on post-transplant health care utilization. We studied this association in a cohort of 1001 consecutive kidney transplants. Methods: We retrospectively reviewed 2011–2015 data from a prospectively-maintained kidney transplant database from a single center. Results: A total of 1001 patients underwent kidney transplant, and were dismissed from the hospital in 3 groups: Early [≤2 days] (19.8%), Normal [3–7 days] (79.4%) and Late [>7 days] (3.8%). 34.8% of patients had living donor transplants (Early 51%, Normal 31.4%, Late 18.4%, P < 0.001). Early patients had lower delayed graft function rates (Early 19.2%, Normal 32%, Late73.7%, P = 0.001). By the hospital dismissal group, there were no differences in readmissions or emergency room visits at 30 or 90 days. Glomerular filtration rate at 12 months and rates of biopsy-proven acute rejection were also similar between groups. The timing of hospital dismissal was not associated with the risk-adjusted likelihood of readmission. Early and Normal patients had similar graft and patient survival. Late dismissal patients, who had higher rates of cardiovascular complications, had significantly higher late mortality versus Normal dismissal patients in unadjusted and risk-adjusted models. Conclusion: Dismissing patients from the hospital 2 days after kidney transplant is safe, feasible, and improves value. It is not associated with excess health care utilization or worse short or long-term transplant outcomes.